Kiribati : 2018 Article IV Consultation -Press Release; Staff Report; and Statement by the Executive Director for Kiribati. (IMF Staff Country Reports; Country Report ;, 2019)
Growth has been strong in recent years and some moderation is expected, with risks skewed to the downside. High fishing revenues improved the fiscal position, but generated pressure to increase spending. There has been progress on fiscal and structural reforms. Yet, public spending needs are large, driven by an infrastructure gap and climate adaptation costs, and the country remains at high risk of debt distress.